Harmonization of Mining and Environmental Regulations as an Effort to Strengthen Legal Protection for Local Populations in Indonesia (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2025)
The exploitation of natural resources through mining projects in Indonesia often has an impact on the lives of residents, both socially, economically, and environmentally. Although the government has established various regulations to protect the rights of affected communities, the implementation of this legal protection still faces various challenges. In this context, this research aims to analyze legal protection for residents in mining projects in Indonesia and examine the effectiveness of regulations that have been implemented. This research uses a normative juridical method using both a statutory and a conceptual approach. The former involves examining multiple legal provisions that govern mining and community protection, including Law Number 4 of 2009 concerning Mineral and Coal Mining, Law Number 32 of 2009 concerning Environmental Protection and Management, and various derivative regulations. The latter involves investigating legal theories that are pertinent to the defense of residents' rights, including the notion of sustainable development, the right to a healthy environment, and the rights of indigenous peoples to land and natural resources. This research does not involve case studies or interviews, but focuses on a normative study of the applicable legal system. Through an analysis of national and international legal instruments, this research is expected to provide academic contributions in identifying weaknesses in existing regulations and providing recommendations for policy makers in improving legal protection for residents affected by mining projects. Thus, this research can be a basis for strengthening more effective legal protection in maintaining a balance between the exploitation of natural resources and the rights of local communities.